Pembelajaran Pianika Dengan Menggunakan Metode Tutor Sebaya Di SMP N 9 Padang - Yulia Sesmita; Harisnal Hadi (SENDRATASIK UNP, 2019)
This article aims to describe the implementation of learning music pianika using peer tutors in Class VII.5 at 5 SMP Negeri 9 Padang. This type of research is qualitative research using descriptive method. The main instrument in this study is the researchers themselves and assisted with the instrument's supporters such as stationery and photo cameras. Types of data using primary data and secondary data. The technique of data collection is done by way of observation, interview, documentation and study of the literature. Stages of analyzing data is grouped data, clarifying data and describes the data. The results showed that Learning pianika, using the method of Peer Tutors SMP Negeri 9 Padang Kelas VII.5 already carried out in accordance with what is expected. Results achieved students from daily value 95% student satisfaction in learning material pianika and also can we compare with the results of student learning using conventional methods before learning the results with only 70%. Art Learning culture can be summed up with a peer tutor methods approach with the basic concept of the game a simple musical instrument individually very precisely made.